Detection of deteriorating patients after Whipple surgery by a modified early warning score (MEWS) - Yu, Min (Ann Transl Med, 2019)
BACKGROUND: The modified early warning score (MEWS) was set up to supply prompt recognition of clinically deteriorating patients before they undergo a severe and life-threatening event. The study aimed to describe the probable usefulness of the MEWS in identifying deteriorating post-Whipple patients in hospital wards. METHODS: We performed a study to analyze the relationship between the vital parameters and postoperative severe adverse events of patients after Whipple surgery in Guangdong Provincial People’s Hospital from 2000 to 2017. In the retrospective study, a total of 13,651 sets of vital parameters in 236 Whipple postoperative patients were included. Subsequently, we applied a MEWS scoring system and explored the accuracy of the MEWS in evaluating the patients’ final events versus advanced mathematical models. We then put the MEWS into the ward warning system and confirmed the accuracy of the MEWS based on the results of prospective studies again. RESULTS: We assessed the ability of the MEWS to predict postoperative complications with an accuracy rate of 90.86–91.23%, a sensitivity of 83.04–90.88%, and a specificity of 90.85–95.73%. CONCLUSIONS: The MEWS model was applied to identify post-Whipple patients at risk of complication. Once the MEWS ≥2, interventions were needed to minimize the adverse events. Our data suggest that the MEWS is comparable to the advanced mathematical models, but MEWS is more accessible to perform and more generally applicable.